2018
DOI: 10.25258/phyto.v9i07.11155
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antibacterial Activity, FTIR and GCMS Analysis of Ceropegia juncea Roxb.

Abstract: The present study was focused on the preliminary phytochemical, antibacterial activity, FTIR and GC-MS analysis of aerial parts of C. juncea. Phytochemical analysis of three extracts showed that the presence of alkaloids, tannins and flavonoids. The methanol extract of aerial parts were found to be exhibit highest zone of inhibition against S. aureus (19.3mm), P. florescence (17.6mm) and K. pneumonia (17.0mm). FTIR analysis of the methanol extract given the major peak observed was at wavenumber 3354.08cm-1 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The crude extract (10 mg) was dissolved in 5 ml of the respective solvent to make a stock solution. From the stock solution 1 ml of solution was taken and diluted by adding 9 ml of the respective solvent following the methodologies of Adinew (2014) and Visveshwari et al (2017). The samples were then exposed to GC–MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The crude extract (10 mg) was dissolved in 5 ml of the respective solvent to make a stock solution. From the stock solution 1 ml of solution was taken and diluted by adding 9 ml of the respective solvent following the methodologies of Adinew (2014) and Visveshwari et al (2017). The samples were then exposed to GC–MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular phylogenetic analysis of 81 Ceropegias aligned them in many clades (Surveswaran et al., 2009). The methanol extract of C. juncea are medicinally valuable and possess various pharmaceutical applications (Visveshwari et al., 2017). It can be concluded that insufficient study has been done so far on C. anjanerica, As the species has ornamental and medicinal potential, conservational actions should be undertaken.…”
Section: Threat and Conservation Statusmentioning
confidence: 99%